Development of Trichodermin Nanoemulsion Based on Medium Chain Triglycerides as Antifungal of Ganoderma boninense in vitro - Muhammad Alwin Azhari; Ike Wahyuni Putri; Ahmad Irvan Pratama; Radika Evita Hidayah; Laksmi Ambarsari (IPB University, 2017)
Trichodermin has antifungal activity against Ganoderma boninense, but it is volatile and insoluble in water. Research on trichodermin as antifungal G.boninense has been done, but not yet at the stage of altering the nature of the compound. This study aims to develop trichodermin as antifungal G. boninense in the form of nanoenkapsulat with observed aspects including formulation, encapsulation, characterization, and antifungal activity. Trichodermin is extracted from Trichoderma harzianum by maceration. Nanoemulsion is made using Emulsion Inversion Point (EIP) method and encapsulation is done by spray drying. Antifungal activity was tested using a modified dual culture assay method. The results showed the rendement of trichodermin extraction of 0.70%. The best nanoemulsion formula is nanoemulsion with Tween 80 concentrations of 75% of the total organic phase. The formula nanoemulsi has a size of 231.95 nm, polydispersity index of 0.348, and zeta potential of -35.6 mV. Encapsulation has a yield of 5.79%. The encapsulated powder has a moisture content of 5.79%, contains a typical functional group of trichodermin compounds, and is round with an uneven surface. The antioxidant activity of nano-trichodermin encapsulation is higher than trichoderminextract and positive control (hexaconazole) with PIRG value of 84.40%.